Clinical analysis of anlotinib as first-line treatment for elderly patients with advanced lung adenocarcinoma without driver gene mutations. Issue 1 (January 2022) - Zhu, Jinxiu; Xie, Qiang; Zhong, Aihong; Le, Yuyin
Abstract : This retrospective study was conducted to explore the effects of anlotinib as first-line treatment for patients with advanced lung adenocarcinoma. We retrospectively reviewed medical records of 60 patients with advanced lung adenocarcinoma, admitted to the Fuzhou Pulmonary Hospital between August 2018 and December 2019. We calculated and recorded the objective remission rate (ORR), disease control rate (DCR), adverse reactions, quality of life assessment, progression-free survival (PFS) and overall survival (OS) for each group. We applied χ 2, Mann–Whitney U test, Kaplan–Meier and log-rank statistical methods as appropriate to analyze the data. We found no statistically significant differences in either ORR (17.5 vs. 15%) or DCR (67.5 vs. 65.5%) between the anlotinib and pemetrexed groups ( P > 0.05). The adverse reactions graded ≥3 in the anlotinib group were fatigue and diarrhea and they accounted for 5% of all the adverse reactions in the group. The patients in the anlotinib group presented better physical, role, cognitive, emotional, and social functions than those in the pemetrexed group ( P < 0.05). The symptoms of fatigue, nausea and vomiting, loss of appetite and constipation in the anlotinib group were significantly less frequent than those in the pemetrexed group ( P < 0.05). We found similar median PFSs (3.0 vs. 2.8 months) and median OSs (7.0 vs. 7.0 months) in both treatment groups ( P > 0.05). The choice of anlotinib as first-line chemotherapy for treating elderly patients with advanced lung adenocarcinoma was effective, safe; the treatment was better than other drugs at improving the patients' quality of life.